Обґрунтування параметрів решета для сепарації зерна - Лузан, П. Г.; Лузан, О. Р.; Петренко, Д. І.; Luzan, Petro; Luzan, Olena; Petrenko, Dmitry (КНТУ, 2016)
В роботі запропоновано методику обґрунтування параметрів та визначення умов проходу часток зернової суміші крізь щілини решета, виконаного з набору стержнів, що розширюються у бік руху оброблюваного матеріалу. Встановлено, що на показник кінематичного режиму найбільше впливають початкова швидкість руху оброблюваного матеріалу та радіус решета, зміною яких можна добиватися необхідної ефективності сепарації. Визначено умови проходу часток оброблюваного матеріалу крізь щілини решета та умови, коли вони в них не застрягають. The objective of this work is to develop a method for substantiation of parameters along with determination of conditions for passing grain particles through the sieve openings, diameter of which is increasing toward work material movement and made with set of rods. It has been defined that the biggest impact on kinematic movement parameters has the starting speed of work material movement and the radius of a sieve and by changing this parameters the required effectiveness for this type of sieves can be achieved. The conditions of passing of work material particles through sieve openings without blocking the openings were defined. The increase of kinematic movement parameters takes place with the increase of starting speed, while increase of a radius has an opposite impact. The usage of offered sieves increase separation effectiveness by 12-14% compared to regular sieves.
Substantiation of sieve parameters for grain separation
Keywords: зерноочисна машина; решето; сепарація; критерій Фруда; очищення зерна; забивання решіт; зерно; separator; sieve; separation; Froude number; grain separation; sieve openings blocking; grain